Quantitative and Qualitative Tools in Studies on Pelvic Floor Muscle Rehabilitation - Abasali Pourmomeny; Samaneh Alebouyeh; Anahita Torkzadeh (Vesnu Publications, 2017)
Introduction: Rehabilitation is the treatment of choice for biomechanical problems of the pelvic floor muscle. The rehabilitation and assessment tools used in lower urinary tract symptoms are dependent on the pathological nature of the illness and the cultural background of the patient. The aim of the present study was to review and introduce the research and clinical instruments for rehabilitation in lower urinary tract symptoms. Materials and Methods: A computerized database search was performed in Pubmed, Medline, Cinhal, and Science Direct using the keywords lower urinary tract symptoms, urinary incontinence, rehabilitation, pelvic floor muscle training, over active bladder, physiotherapy. Clinical trial articles which had evaluated the effect of rehabilitation were included in this study. Articles written in any language other than English were excluded from the study. The source of each tool was determined and described, and each collection tool was evaluated. Results: It was found that 181 clinical trials have been published between 2000 and end of 2016; 142 articles were related to urinary incontinence. On prostate surgery and overactive bladder, respectively, 18 and 14 papers were obtained. 71% of the studies used at least one questionnaire related to the quality of life (QOL). In some researches, pad test and other tools were used. Conclusion: Although quantitative tools are utilized in rehabilitation studies, questionnaires, especially QOL questionnaires, have an important role in evaluations.